2022
DOI: 10.3389/fpubh.2022.903431
|View full text |Cite
|
Sign up to set email alerts
|

An Estimation of the Effect of Green Financial Policies and Constraints on Agriculture Investment: Evidences of Sustainable Development Achievement in Northwest China

Abstract: Farming' community actively participating as micro-actors in green finance schemes is critical for regional planning and development. On the basis of the extent to which financial progress and sustainable development are coordinated, in a difference-in-differences approach, this article employed 2350 small investigations to estimate the influence of green-finance strategies on peasants' agriculture investment and developed a mediation effect method. It investigates the role of peasant managerial variability in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Mei et al (2020) conducted a sample survey to examine the constraining role of finance in agricultural green development. The research revealed that finance had a certain degree of inhibition on agricultural green development, necessitating financial reform to alleviate its inhibitory effects on agricultural green development [41].…”
Section: Research On Factors Influencing Agricultural Green Developmentmentioning
confidence: 99%
“…Mei et al (2020) conducted a sample survey to examine the constraining role of finance in agricultural green development. The research revealed that finance had a certain degree of inhibition on agricultural green development, necessitating financial reform to alleviate its inhibitory effects on agricultural green development [41].…”
Section: Research On Factors Influencing Agricultural Green Developmentmentioning
confidence: 99%
“…In our study, the regional limiting factors of AGD, analyzed by the obstacle degree model, could be neglected in larger-scale evaluations, which often cover spatial differences and individual problems. Based on a literature review, the factors influencing AGD can be categorized into economic, political, technological, and other factors [22,86]. The main limiting factor influencing the AGD level in Beijing ECDA was AP7, with the exception of 2009 (Table 2).…”
Section: Factors Influencing Agd Levelmentioning
confidence: 99%
“…The smaller the gap between the levels of economic development, the more favorable it is to increase the total green factors in agriculture [33,34]. The impact of regional finance on agricultural green total factor productivity in China has also proved that agricultural investment flows are needed in the agricultural sector [86,87]. Rani et al [88] and Lei et al [89] stated that the misallocation of agricultural capital affects the efficiency of agricultural green production as well.…”
Section: Factors Influencing Agd Levelmentioning
confidence: 99%
“…Many agricultural credit funds have been used to improve agricultural production technology, ignoring the improvement of agricultural technology efficiency, resulting in the uneven allocation of agricultural credit funds (Wen and Wang, 2022). On the other hand, the expansion of the agricultural credit scale is divorced from the actual needs of agricultural business entities, and there are situations where agricultural business entities divert credit funds for other purposes, resulting in more overdue loans, affecting the enthusiasm of financial institutions to provide credit funds in agriculture (Mei et al, 2022). Thirdly, the agricultural credit scale significantly impacts the AGPE in the eastern region, followed by the central and western regions.…”
Section: The Impact Of Agricultural Credit Scale On Agpementioning
confidence: 99%